Plus ultra: o corpo no limite da comunicação - Araujo, Oriana Maria Duarte de (2012)
In the last twenty years, much has been said about the limits of communication. Researchers such as Muniz Sodré, Helena Katz and Christine Greiner have discussed designations (biomedia and bodymedia, among others) to describe what can be considered a new field of research and its respective processes of sensitive communication. To this end, the starting point is microcommunication, perceptions and the production of subjectivities. These studies combine transdisciplinary networks whose analyses unite cognitive actions of the body, performative actions and their respective political implications for daily life. In tune with Michel Foucault s proposals (1984; 1985; 1988; 2006; 2011), a biopolitical communication that is, above all, organized on bodymedia, is sought. To transit through these epistemological fields, this thesis presents a theoretical construction that builds on the authors cited, relating them to practical experiments that tested, over four years, the limits of corporal communication based on rowing activities in rivers in five regions of Brazil. The material was documented in different medias, generating videos, drawings, text and photographs that constitute the body of this research